Peningkatan Kemampuan Literasi Sains Dan Teknologi Melalui Model Pembelajaran Sains Teknologi Masyarakat - Julfi Adrian Nugraha; Sulistyono Sulistyono; Uus Toharudin (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
The purpose of the research is to get the description of science literacy skill and technology after the learning process through science technology society  learning model in the sub-concept of water pollution. The method that I used is free eksperimental and the sample of the research is the class X of MIPA 4 from the population of the class X SMAN 2 Indramayu. The research instruments are observation sheet which purposing in analyzing the science literacy and technology of the student, multiple choice consisting of 20 questions which are given through pretest and posttest, and questionnaire which analyze the student’s response after the learning. The observation result shows that in the science technology society  learning model have few obstacles: inadequate of facilities and infrastructure, students’ lack of the knowledge, lack of preparation and lack of time. In general, the students are quite capable to do three kinds of the science literacy aspects and two kinds aspects of technology literacy. The three aspects of science literacy includes: explanation in regards to the scientific phenomena, designing and evaluating scientific exploration, and the use of scientific evidence. Technology literacy includes: management and evaluation of information gathers from all source of media and understanding the utilization of technology. Learning through Science technology society  model can improved the student’s science and technology literacy in gaining knowledge, skill and attitude. The knowledge that the student get are more meaningful and will be longer lasting in their mind. Based on the analyisi the mean Pretest  is 49,5 and the mean  () posttest is 70,7. After that, I conducted the test of t and the result is thitung (0,86) ttabel (0,05), which means this is significantly different. The analysis of questionnaire shows that most of the students give positive response to the indicator with the mean of them is more than 75%Keywords: Science Literacy; Technolgy Literacy; Science technology society; Water Pollution